2000
DOI: 10.1063/1.1309053
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo approach to phase transitions in ferroelectromagnets

Abstract: A Monte Carlo algorithm based on the hybrid Ising-DIFFOUR model is proposed to investigate the phase transition in ferroelectromagnetic lattice in which the ferroelectric order and antiferromagnetic order coexist below a certain temperature. The Ising spin moment and ferroelectric displacement and their susceptibilities as well, as a function of temperature for systems of different magnetoelectric couplings, are simulated and compared with the mean-field approach. The typical antiferromagnetic transition at Né… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…3, in which the ME coupling coefficient g is given as 0.022, 0.025, 0.028. We find that the average polarization experiences an anomaly at T N , indicating the contribution of ME coupling, which qualitatively agrees with the results of former researches [12,16]. From the figure, we can find that, when ME coupling is stronger, T N becomes higher.…”
Section: Mean-field Theorysupporting
confidence: 92%
See 1 more Smart Citation
“…3, in which the ME coupling coefficient g is given as 0.022, 0.025, 0.028. We find that the average polarization experiences an anomaly at T N , indicating the contribution of ME coupling, which qualitatively agrees with the results of former researches [12,16]. From the figure, we can find that, when ME coupling is stronger, T N becomes higher.…”
Section: Mean-field Theorysupporting
confidence: 92%
“…The spin configuration of the nearest-neighbor Mn ions forms the triangular lattice structure in the basal plane with the nearest-neighbor Mn spins rotate 120 from each other. Given that the hexagonal phase of RMnO 3 may be transformed in condition of a high temperature and pressure to the orthorhombic perovskite-type structure, the ME properties related with the external electric (or magnetic) fields have been studied by the model of A-type antiferromagnet with the FM intraplane interaction and the AFM interplane one [15,16]. However, for the case of a real situation, we would better take the triangular magnetic structure in the basal plane into account.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of magnetoelectric coupling is particularly strong when temperature is close to or just below magnetic phase transition temperature and may result in a change of electric properties [4][5][6]. In recent studies, it has been found that pair correlation between magnetic lattice sites, hereafter referred to as magnetic correlation for brevity, played an important role on the electric properties [7][8][9][10][11], and there have been theoretical works devoted to the investigations of this effect [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Then, several macroscopic approximations were put forward to explain magnetoelectricity, most of them based on Landau's phenomenological theory. X. S. Gao 9 and J. M. Liu 10 simulated the dielectric and magnetic properties of multiferroic materials based on a microscopic model proposed by Janssen in 1994 11 for the magnetoelectric coupling using the Monte Carlo (MC) method.…”
Section: Introductionmentioning
confidence: 99%
“…It will also be assumed that the magnetic and electric systems mutually interact between them. Following the models of Janssen 11 and Gao 9 the Hamiltonian for the system may be written as:…”
Section: Model and Simulationmentioning
confidence: 99%